Identifying and determining the spatial organization model of CBD\'s (Case Study: Mashhad Metropolis) - mohammadreza mirsaeedi; moslem seyed alhossaini; Fereshteh Ahmadi; Amir Hossain Shabani (تحقیقات کاربردی علوم جغرافیایی)
Generally speaking the existence of metropolises, alongwith the high various business districts have led to high valume of travels to these centers.The density and separation of these centers brings about the increase and the decrease of the vehicles. The adoption of location determination strategies and that of the comunicational centers and the city activities has made the cities continue the developement process while cosidering the fairly service destribution and the spatial equalities.The goal of this research is the recognition and determination of the city spatial organization working centers and activity model and the relation of service functioning with one another so that the mono central and poly central cities can have a important effect on the destribution system and service centers and the vast changes of the citizens .The analysis method is a kind of quantity and quality one. In the quality part of that the descriptive statistics ( the geometrical presentation , graphical disparation, the centralism measures) and the Hansen Model. In the areas of planning, a great difference is seen in the levels of land uses so that the land use of higher educations in the western metropolitan city of Mashhad area is 84 percent while that of the eastern area is 3 percent. It is the same about the equipped medicinal, commercial and green space areas.Only in the areas of managerial levels  there is a relative balance. Finaly the city is devided by three areas throughwhich while considering the employment , the developement potential and distance , the land use determining rate was found out.